The Influence of Packaging Attributes on Customer Buying Decision - Lim, Kim Yew; Chen, FengQiao; Wong, Chee Hoo; Rosmini, Omar; Tan, Owee Kowang (INTI International University, 2020)
Past studies reveal that efforts on the packaging strategies have become an increasing powerful marketing tool to attract customers. Packaging attributes such as packaging graphics, package designs, colors, shapes and pictures attracts consumers’ attention to a particular brand and influences consumer’s perceptions about product. However, the main objective of the present study is to examine the packaging attributes affecting the customers buying decisions. Specifically, this study focuses on the relationship between packaging color, packaging material, printed information on customers buying decision. The data of this study is collected using survey questionnaire and The Statistical Package for Social Science (SPSS) software is adopted to analyze the collected data. This study reveals that customers viewed printed information of products as the most important factor that influence buying decision. Meantime, finding from this study also reveals that packaging material is less influenced by the customer buying decision. The implication of the study is that marketers shall place printed information as the marketing focus when dealing with car marketing strategy towards potential customers.